Sistemas de recuperación de información - Ordoñez Salinas, Sonia; González O., Fabio A. (Ingeniería, 2003)
This document presents a survey of the main contributions that has been made in the topic of the Information Recovery systems (IR). Since the efficiency and the performance of this systems depend on several subsystems that have been growing and suffering changes in an independent way, this survey is organized around four broad thematic areas: representation of documents and queries, data structures, selection of relevant documents and efficiency of Recovery Systems. Finally IRS based en semantics are discussed.